BOBOT BADAN DAN UKURAN TUBUH SAPI PERAH BETINA FRIES HOLLAND DI WILAYAH KERJA KOPERASI PETERNAK GARUT SELATAN - Asep Permadi Gumelar; Rian Aryanto (BUANA SAINS, 2011)
Experiment was conducted from Juli until August 2011. The aims of this experiment is to obtained, study and to find out about weight and size of body female cattle diary Fries Holland at area of Cooperative of South Garut Husbandary in region of Garut. Survey methodology was used to observation and measure weight, size of female diary cattle. Research result showed that female diary cattle have weight about 307,68±21,85 kg; KV 7,1%; LD 157,23±3,88 cm; KV 2,47%; TP 121,63±3,28 cm; KV 2,70%; PB 127,92±3,11 cm; KV 2,43%; LeD 29,74±1,18 cm; KV 3,97% and LeP 36,59±1,73 cm; KV 4,74%. Evaluation continued by using table distribution also showed point 1,68 with t value for BB 2,30; LD 3,77; TP 13,25; PB 6,17; LeD 4,13 and LeP 2,22. It is concluded that evaluation of weight and size of body female diary cattle was accepted due to value of point higher compared with table distribution